Anaesthetic management of primary hyperparathyroidism with hypercalcaemia and multiple bone fractures for excision of parathyroid adenoma - Koirala, Sabin; Shrestha, Gentle Sunder (Journal of Society of Anesthesiologists of Nepal, 2015)
Calcium is important for maintaining numerous physiological processes many of which are important for anaesthesiologists. Primary hyperparathyroidism is an important cause of hypercalcaemia which can be associated with multitude of systemic problems. Our patient presented with complains of spontaneous fracture of bones, associated with pain in small joints since nine months. Later, she developed weakness all over the body and had obvious deformities in both extremities making her unable to perform her daily activities. Her total serum calcium, serum phosphorus and serum parathyroid hormone levels were elevated. She was diagnosed as severe hyperparathyroidism with hypercalcaemia, multiple bone fractures and deformities and was planned for excision of parathyroid adenoma. Management of hypercalcaemia was initiated preoperatively and was continued in intra-operative period. Meticulous attention was paid on patient positioning and prevention of further bone fractures. We used Dexmedetomidine to supplement anaesthetic agents, to facilitate smooth recovery and to prevent post-operative shivering. Close monitoring of electrocardiogram and neuromuscular function was done. Vigilant monitoring was done to detect possible postoperative complications, including hypocalcaemia. We present this case to discuss the complexity of problems that primary hyperparathyroidism can manifest and the related anaesthetic concerns. Journal of Society of Anesthesiologists of Nepal 2015; 2(2): 87-90